The political power of economic elites in contemporary Western democracies - Alberto Parmigiani (United Nations Research Institute for Social Development (UNRISD), 2022)
This paper employs a multidisciplinary social sciences approach to analyse the political power of contemporary economic elites in the political sphere of Western democratic countries. Economic elites are defined as the wealthiest members of society characterized by their disproportionate access to or control over economic resources, and their ability to convert them, directly or indirectly, into power or influence. This paper makes use of the classical concepts of structural and instrumental power to explain the sources of their influence in democratic decision-making processes. I claim that a powerful and distinctive trait of elites lies in their high internal cohesion in the steadfast defense of their interests. Connecting different streams of literature, I contrast elites' awareness of their power in the political struggle around inequality and redistribution, interpreted as an element of cohesion, with misperceptions about inequality on the part of average citizens, a common finding in recent research on this issue. Hence, I propose this cognitive divide between average citizens and economic elites as an innovative angle to look at the classical puzzle of high inequality combined with low demand for redistribution. The paper then reviews the political science literature on the ability of the wealthy to obtain their political objectives and influence the democratic legislative process. The income and wealth bias in political representation has been empirically demonstrated in the United States and, preliminarily, in some European countries. The findings show that the preferences of average citizens have little or no effect on the policy changes enacted in many Western mature democracies. The paper carefully surveys the possible explanations proposed for this relevant finding. Finally, I argue that economic elites constitute a cultural hegemony by creating and reinforcing institutions and beliefs that shape or maintain the extremely unequal distribution of political and economic resources. Effectively, the richest part of society has been able to impose its ideas through a long-term agenda-setting approach that entails the formation of networks of cultural organizations to sustain the legitimacy of inequality. Today's highly unequal status quo has been facilitated by this process, together with a series of feedback effects from political decisions that have simultaneously further increased inequality and corroborated public opinion about its inevitability. Policies that have increased inequality from the 1970s onwards have shaped the perception of inequality, creating social acceptability around the idea of individual freedom and delegitimizing government welfare expenditure. This change in public attitudes has enabled the policy space for even greater inequality, in a cyclical mechanism that is very hard to break.
Keywords: 330; Cultural hegemony; economic elites; inequality; neoliberalism; perceptions; power